Transformation of Exclusive to Inclusive Spaces: The Case of Al-Hikmah 2 Benda Islamic Boarding School, Brebes - Agung Kurniawan; Nensi Golda Yuli (Journal of Architectural Research and Design Studies, 2021)
The history of public recognition of pesantren is closely related to the existence of figures in a pesantren. However, in today's development, various needs and challenges require pesantren to adapt in order to maintain their existence. The increasing number of students followed by various developments in needs and efforts to increase protection are the reason why a number of traditional pesantren transforming their spatial concept. This design transformation was carried out from open (inclusive) to closed (exclusive). On the other hand, this condition has implications for the role of pesantren in community empowerment. This is what happened at the Al-Hikmah 2 Benda Islamic Boarding School, one of the Islamic boarding school that has transformed its space from open to closed. From the existing background, the reasons and objectives of the researcher are to 1). Trace the inclusive and exclusive concepts that have been used by the AlHikmah 2 Benda Islamic Boarding School. 2). Analyze the impact of the application of concepts that have been used on pesantren and society. The research method used is naturalistic, with a key instrument is the researcher. The research results showed that the inclusive and exclusive concepts that have been used by the Al-Hikmah 2 Benda Islamic Boarding School were obtained, as well as the implications of the advantages and disadvantages of applying each of these concepts. Inclusive Islamic boarding schools have advantages in socio-economic interactions and the role of community empowerment but are constrained in efforts to protect students and community recognition, while the concept of exclusive pesantren has advantages in anticipating the protection of students but the role of pesantren in community empowerment is limited. However, there are inclusive spaces found in the exclusive layout of the AL-Hikmah 2 Benda Islamic Boarding School. These spatial concepts and models can be used and developed to deal with problems that arise from the application of each existing concept.Keywords: Community development; exclusive spaces; inclusive spaces; Islamic boarding schools; student's protection.